IMPLEMENTASI WAWASAN KEBANGSAAN DALAM PEMBELAJARAN SEJARAH DI PONDOK PESANTREN - Anis, Madhan; Haikal, Husain; Joebagio, Hermanu (HISTORIKA, 2016)
Background: This study has the objective to (1) describe the history lesson planning, (2) describe the implementation of the teaching of history, (3) describe the history of learning assessment, and (4) analyzing the constraints in the implementation of national awareness-based teaching history in high school Al -Muayyad which is one unit of formal education in Pondok Pesantren Al-Muayyad SMA Muhammadiyah Surakarta and Boarding School, which is one unit of formal education in Modern Boarding School Boarding School Muhammadiyah Yogyakarta.Methods: The study was a descriptive qualitative study of the strategies are rooted double case. Footage used in this research is purposive sampling with criterion-based selection. Data was collected through direct observation, in-depth interviews with teachers and students of class XI IPS, and recording documents such as learning devices. Data validation performed by triangulation. Analysis of the data used is interactive model, namely data collection, data reduction, data display and conclusion.Results: This study concluded that (1) Planning made educators in high school and high school Al-Muayyad MBS in history teaching based national vision is to construct a learning tool in the form of a syllabus and lesson plan (RPP) which incorporate cultural values and national character . (2) The implementation of national awareness-based history of learning is done in high school educators Al-Muayyad through heroic story boarding in upholding the independence of Indonesia, question and answer, and discussion groups. While the implementation of national awareness-based history of learning is done in high school educators MBS through documentary film history of national struggle, question and answer, discussion groups, and assignment (3) The form of the assessment test and non-test by considering the cognitive, affective and psychomotor student. (4) The problem faced in teaching history in high school national awareness-based Al-Muayyad and senior MBS including the ability of teachers in the learning process, the attitude of students in participating in the learning and teaching facilities.